2020
DOI: 10.2147/ott.s275327
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuropilin-1 Interacts with Fibronectin-1 to Promote Epithelial–Mesenchymal Transition Progress in Gastric Cancer</p>

Abstract: Introduction: Neuropilin-1 (NRP1) binds to many ligands and co-receptors and affects cell survival and migration, which is essential for tumor progression. However, there are still largely unknowns about how NRP1 affects the epithelial-mesenchymal transition (EMT)related malignant progression in gastric cancer. Methods: We used TCGA to analyze the expression of NRP1 in gastric cancer and its impact on patient survival. In in vitro experiments, transwell, wound healing and colony formation assays were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…FN1 was found overexpressed in some cancers, such as esophageal cancer and cervical cancer 34,35 . FN1 overexpression promotes gastric cancer cell migration and invasion 36 . Suppression of FN1 hampers malignant progression of colorectal carcinogenesis by inhibiting cell proliferation, migration 37 .…”
Section: Discussionmentioning
confidence: 99%
“…FN1 was found overexpressed in some cancers, such as esophageal cancer and cervical cancer 34,35 . FN1 overexpression promotes gastric cancer cell migration and invasion 36 . Suppression of FN1 hampers malignant progression of colorectal carcinogenesis by inhibiting cell proliferation, migration 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Assessing EMT state in tumors is challenging as the process is transient and reversible (24). Previous studies have focused on exploring the biological functions and molecular mechanisms of EMT-related genes, such as the expression of E-cadherin, claudins, ocludins, and cytokeratins, and considered these genes as common markers of epithelial state, and Vimentin (VIM), fibronectin, and a-SMA as the markers of mesenchymal state (25)(26)(27). However, for some circulating tumor cells (CTCs) underwent EMT, the expression of these (25-27) epithelial cell adhesion-based molecular markers is difficult to be detected (28).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has demonstrated that NRP-1 was frequently overexpressed and associated with poor prognosis in gastric cancer, melanoma, bladder cancer, cervical cancer, hepatocellular carcinoma, as well as breast cancer [ 28 - 33 ]. Our previous studies demonstrated that NRP-1 acts as an oncogene in breast cancer progression [ 5 - 8 ].…”
Section: Discussionmentioning
confidence: 99%